Decoding Food Labels: Tools for People with Food Allergies - Elizabeth A. Gollub; Amy H. Simonne (EDIS)
The goal of this publication is to provide information to help consumers understand ingredient statements on food packages, so they can avoid foods and food-products that might contain specific allergens. It also differentiates between allergies and intolerances, and discusses the potential for cross-contamination of foods both in and away from the home. This document is FCS8781, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611. First published: November 2004.